Assistance in Stock Opname System Management in Goods Inventory at PT Mega Niaga Sejahtera - Nunuk Novianti; Kadek Vishnu Bhuana; Layon Hutagaol (Syntax Literate, 2023)
This Community Service aims to provide training and understanding of inventory stock taking system management through a three-month mentoring program from May to July 2023 at PT Mega Niaga Sejahtera. The methodology employed in this report is a qualitative descriptive method involving direct observation, practical implementation, and interviews with the Partner, along with references from journals, theses, and literature books. The results of the Community Service revealed discrepancies in the stock taking outcomes in June 2023 due to the improper implementation of company procedures and recording systems. Hence, there is a need for enhanced supervision of inventory recording systems in accordance with company standards. Regular daily recording and conducting stock taking with minimal discrepancies during implementation are crucial to ensuring accurate financial reporting. Timely execution of stock taking will facilitate adherence to predetermined schedules, yielding swift and accurate data through an application linked to the system, enhancing financial accountability.